FORMULASI SEDIAAN SABUN PADAT EKSTRAK ETANOL KULIT BUAH PEPAYA (CARICA PAPAYA L.) - Mega Yulia; Liandri, Vanessa; Mulyani, Dwi (Jurnal Pharmacopoeia, 2024)
Papaya skin (Carica papaya L.) has antibacterial activity against Staphylococcus aureus bacteria and Escherichia coli bacteria. This research aims to find out whether papaya peel extract can be formulated into solid soap. Solid soap preparations were made in 4 formulas with F0 (formula 0) as the base and the addition of papaya peel extract at Fl (formula 1) 3.5 g, FII (formula 2) 7 g, and FIII (formula 3) 10.5 g. The formulated solid soap preparation is subjected to physical evaluation including organoleptic, pH, foam height tests, water and free alkali content. The research results showed that all formulas met the requirements except for the water and free alkali content tests which did not meet the requirements because they still exceeded the maximum limit for free water & alkali content set by SNI 2016.